Impact analysis of an Optical Character Recognition Enhanced Information Retrieval Tool using the combination of Task-Technology Fit Model, Technology Acceptance Model and Information System Success Model - Surmieda, Janny S.; Dorado, Dan Anthony D.; Cabbab, Johann Frederick, A.; Obille, Kathleen Lourdes B.; Santos, Mark Anthony A.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2019)
Ranganathan notably described the library, perhaps could also include information centers - as a growing organism. As with the advent of an era filled with technology use, information center needed to evolve and update the way we provide and locate information. With this in mind, proposed information retrieval tool equipped with optical character recognition was developed and tested in this study. Using the combination of task-technology fit model (TTF), technology acceptance model (TAM) and information system success model (IS success model). The research aims investigate the extent of the impact of the proposed information retrieval tool to user performance. A questionnaire was used to gather information and responses from the users of the proposed information retrieval tool. After tabulation of responses, regression analysis was used to determine the significance between each variable.
Results show that - technology fit and information quality have a direct and indirect impact, thru perceived ease-of-use and perceived usefulness to user performance, System quality also exhibits direct and indirect impact, thru perceived ease-of-use to user performance. While service quality exhibits a direct impact on user performance.
Thesis (Master of Library and Information Science)